2016
DOI: 10.1111/papr.12466
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin E‐Mediated Hypersensitivity Reaction to Ketamine

Abstract: This case represents a likely immunoglobulin E-mediated type I hypersensitivity reaction to ketamine, supported by elevated tryptase levels and positive intradermal skin testing. The interpretation of these results and likely mechanism of the hypersensitivity reaction are described. The patient and treating team were advised against subsequent use of ketamine, due to the risk of serious adverse systemic reaction with repeat exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Adverse drug reactions are often immune-mediated hypersensitivity reactions, as opposed to anaphylactic reactions, which are mediated by IgE and classified as type I allergic reactions. 5 , 8 The clinical criteria for anaphylaxis generally include urticaria and one of the following: respiratory distress, hypoxia, hypotension, or associated symptoms of organ dysfunction. Symptoms occur within minutes to hours after allergen exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse drug reactions are often immune-mediated hypersensitivity reactions, as opposed to anaphylactic reactions, which are mediated by IgE and classified as type I allergic reactions. 5 , 8 The clinical criteria for anaphylaxis generally include urticaria and one of the following: respiratory distress, hypoxia, hypotension, or associated symptoms of organ dysfunction. Symptoms occur within minutes to hours after allergen exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Although no tryptase level was confirmed in our case, the temporal relationship of symptoms to ketamine exposure point to significant histamine release and possible IgE-mediated anaphylaxis. 5 However, an in-vitro study performed by Fell et al demonstrated that ketamine directly increases histamine efflux in the brain, without mediation by IgE. 9 One small study used the Prausnitz-Kutzner test to confirm that a ketamine allergic reaction was indeed not mediated by an IgE mechanism, and was more likely to result from direct ketamine stimulation of mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Occasional case reports have demonstrated hypersensitivity reactions to ketamine. [8][9][10][11] This patient developed erythema, face edema and difficulty breathing following the administration of ketamine intravenously. The onset of the reaction was immediate and the intradermal test showed a positive reaction to ketamine, though it was not certain that the patient had previous exposure to ketamine.…”
Section: Discussionmentioning
confidence: 97%
“…Although skin tests are usually performed 4-6 weeks after an acute reaction, it took a great deal of time to explain the necessity of the test to patient's parents. In reference to the literature, a study by Ozcan et al 11 conducted intradermal tests 12 weeks after the reaction. The ketamine concentrations for skin tests vary in different studies.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation